Effect of early adverse events on response and survival outcomes of advanced melanoma patients treated with vemurafenib or vemurafenib plus cobimetinib: A pooled analysis of clinical trial data. (28th February 2019) - Hopkins, Ashley M.; Van Dyk, Madele; Rowland, Andrew; Sorich, Michael J.
Abstract: This study aimed to evaluate the impact of early adverse events on overall survival (OS), progression‐free survival (PFS) and objective response within a pooled secondary analysis of participants treated with first‐line vemurafenib or vemurafenib plus cobimetinib in the clinical trials BRIM3 and coBRIM. The study included 583 participants who received vemurafenib monotherapy and 247 who received vemurafenib plus cobimetinib. Adverse events requiring vemurafenib/cobimetinib dose adjustment within the first 28 days of therapy were significantly associated with OS (hazard ratio (HR) [95% CI]: dose reduced/interrupted = 0.79 [0.65–0.96]; drug withdrawn = 1.18 [0.71–1.96]; p = 0.032), PFS (HR [95% CI]: dose reduced/interrupted = 0.82 [0.67–0.99]; drug withdrawn = 1.58 [0.97–2.58]; p = 0.017) and objective response (odds ratio (OR) [95% CI]: dose reduced/interrupted = 1.35 [0.99–1.85]; drug withdrawn = 0.17 [0.06–0.43]; p = <0.001). Arthralgia occurring within the first 28 days of vemurafenib or vemurafenib plus cobimetinib therapy was also significantly associated with favourable OS ( p = 0.026), PFS ( p = 0.042) and objective response ( p = 0.047).